2018
DOI: 10.1007/s11356-018-3037-4
|View full text |Cite
|
Sign up to set email alerts
|

CO2 bio-fixation and biofuel production in an airlift photobioreactor by an isolated strain of microalgae Coelastrum sp. SM under high CO2 concentrations

Abstract: Microalgae cultivation is a promising approach to remove ambient CO via photosynthesis process. This paper investigates the impact of high CO concentrations (6, 12, and 16%) on algae growth, CO biofixation, lipid and carbohydrate contents, and nutrient removal of newly isolated microalgae, Coelastrum sp. SM. In addition, the ability of microalgae to produce biodiesel at optimal condition was studied. The microalgae were cultivated in wastewater using an airlift photobioreactor. Under 12% CO, the maximum biomas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Few studies have been conducted related to the interaction of pH and CO 2 with microalgalcarbohydrate. Previous study carried out by Mousavi et al (2018) found that the increasing accumulation of carbohydrates of Coelastrum sp. SM up to 17% is replaced by a concentration of 6% of the CO 2 with a 12% (v/v) of CO 2 .…”
Section: Introductionmentioning
confidence: 88%
“…Few studies have been conducted related to the interaction of pH and CO 2 with microalgalcarbohydrate. Previous study carried out by Mousavi et al (2018) found that the increasing accumulation of carbohydrates of Coelastrum sp. SM up to 17% is replaced by a concentration of 6% of the CO 2 with a 12% (v/v) of CO 2 .…”
Section: Introductionmentioning
confidence: 88%
“…In the third stage, carbon dioxide uptake and Spirulina sp. microalgae growth were studied by inputting the solution of culture medium and microalgae into the device, and entering the mixture of air and carbon dioxide with 5% (v/v), at two superficial gas velocities (0.185 and 0.524 cm/s), and atmospheric pressure under the following conditions: with 12:12 light-dark (LD) cycle, temperature (30 ± 2 °C) (Mousavi et al 2018), light intensity 2600 lux/m 2 and 7-day experimental period.…”
Section: Methodsmentioning
confidence: 99%
“…They also observed a further improvement in carbohydrate content up to 54.03% under nitrogen starvation coupled with bicarbonate supplementation conditions [ 159 ]. The effectiveness of directly using CO 2 and other carbon sources such as pentose to improve the carbohydrate content can be found in several other published works [ 160 , 161 , 162 ]. Literature reports that both the source and concentration of CO 2 are important.…”
Section: Microalgal Starchmentioning
confidence: 99%
“…Their results showed that the production of carbohydrates and lipids was increased by the addition of 10% ( v / v ) of pure CO 2 at a flow rate of 5 L·min −1 into the photobioreactor. Other studies reported the effect of CO 2 concentration, namely [ 160 ], which indicated carbohydrate content of 58.45% in Coelastrum sp. SM cultivated in dairy wastewater supplemented with 12% CO 2 , and the study of de Freitas et al [ 162 ], which reported an increase in carbohydrate content of Chlorella minutissima pentoses from 32.5 to 56.8% with 5% pentose supplementation conditions.…”
Section: Microalgal Starchmentioning
confidence: 99%